Communicating Food Security: A Comparative Framing Analysis Of Three Local Media Outlets In Lampung Province - Frasetya, Vito; Nasoetion, Nadya Amalia; Pratama, Prayoga Ardhi; Rakhmadi, Roby (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
This research examines the role of local media in Bandarlampung in analyzing food security information through framing analysis. As one of Indonesia's food granaries, Lampung Province faces complex food security challenges requiring effective communication strategies. Using Robert N. Entman's framing model, this qualitative study analyzed 487 articles from three local media outlets (Lampung Post, Radar Lampung, and Tribun Lampung) published during January-December 2024. The research employed document analysis, in-depth interviews with nine journalists and editors, and focus group discussions with twelve participants. Findings reveal two dominant themes: agricultural production and commodity price fluctuations. Each media outlet demonstrates distinct editorial approaches, with Lampung Post emphasizing local food sovereignty, Radar Lampung focusing on innovation and modernization, and Tribun Lampung prioritizing farmer welfare impacts. The study identifies structural, professional, and contextual factors influencing framing patterns. Analysis of the controversial regional regulation on grain trade restrictions illustrates how divergent media framing creates fragmented public discourse and influences policy processes. Media framing significantly impacts public understanding and policy formulation regarding food security. This research contributes to framing theory application in local media contexts and provides practical implications for improving food security communication strategies in Indonesia.